Mycoplasma genitalium among Young, Urban Pregnant Women - Short, Vanessa L. (Hindawi Publishing Corporation, 2010)
Objective. As the consequences of Mycoplasma genitalium in pregnant women are unknown, we examined the relationship between prenatal M. genitalium infection and SAB. Methods. The presence of M. genitalium was determined by PCR in urine from 82 women who subsequently experienced a SAB and 134 women who maintained their pregnancies past 22 weeks gestation. The relationships between M. genitalium and subsequent SAB, demographic, current pregnancy, and reproductive health history characteristics were evaluated. Results. Compared to women without M. genitalium, women with M. genitalium were more likely to report nulliparity (41.7% versus 17.4%, P = .04), history of pelvic inflammatory disease (27.3% versus 8.8%, P = .08), prior C. trachomatis infection (63.6% versus 36.9%, P = .11,) and problems getting pregnant (18.2% versus 4.4%, P = .10). M. genitalium was not associated with SAB (AOR 0.9, 95% CI 0.2–3.8). Conclusions. Pregnant women who test positive for M. genitalium do not have an increased risk of SAB but report a history of reproductive morbidities.